2021
DOI: 10.2196/22465
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Dietary and Physical Activity Intervention Programs for Patients With Hypertension: Scoping Review

Abstract: Background Hypertension is the root cause of many chronic diseases. Lifestyle changes (ie, dietary alterations and physical activity) are seen to be an important step in the prevention and treatment of hypertension. Educating people through web-based interventional programs could offer an effective solution and help these patients with hypertension in the existing health care scenario. Objective In this study, the researchers conducted a scoping literat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The use of digital technologies for prevention and/or treatment of health conditions, termed digital health interventions, is an emerging and promising approach to support people with hypertension [ 326 , 327 ].…”
Section: Behavioural Interventions Digital Health and Wearablesmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of digital technologies for prevention and/or treatment of health conditions, termed digital health interventions, is an emerging and promising approach to support people with hypertension [ 326 , 327 ].…”
Section: Behavioural Interventions Digital Health and Wearablesmentioning
confidence: 99%
“…Introduce communication technologies to facilitate professional guidance and input or social support (digital spaces to communicate with healthcare providers or peers, SMS messaging) as a standalone digital intervention or integrated into a multicomponent intervention [ 326 ].…”
Section: Behavioural Interventions Digital Health and Wearablesmentioning
confidence: 99%
“…A systemic review of the literature was conducted to identify the preferences and effectiveness of web elements for nutrition education intervention programmes, such as content delivery method, use of notification, and interactivity and was published elsewhere. 21 Additionally, several clinical guidelines were analysed to ensure the content was based on clinical evidence and up to date. Next, the content of the website was modified to suit the ethnicity of the targeted population in this study, which is Malay patients with hypertension aged 18 and above.…”
Section: Methodsmentioning
confidence: 99%
“… 20 A recent study found that most patients use online health information such as the Internet, social media or online courses, compared to the interpersonal approach. 21 The use of health information on the Internet could play an important role in effectively improving one's self-efficacy and self-management skills. For example, a previous study showed the potential use of online guided self-determination programs to improve diabetes self-management in young adults.…”
Section: Introductionmentioning
confidence: 99%
“…Exploring effective blood pressure detection and interventions for hypertensive patients can help to achieve hypertension better, and the literature [13] demonstrated the feasibility of an automated intervention based on textual information to increase physical activity in patients with pulmonary hypertension. The literature [14] suggests that many benefits can be gained from using a web-based diet and physical activity program to treat hypertension that focuses on lifestyle changes. The literature [15] considers Internet-based interventions as promising strategies to promote healthy lifestyle behaviors.…”
Section: Introductionmentioning
confidence: 99%